Meningitis after COVID-19 vaccination, a systematic review of case reports and case series - Amirhomayoun Atefi; Aref Ghanaatpisheh; Amirhosein Ghasemi; Hoda Haghshenas; Kimia Eyvani; Arash Bakhshi; Mohammad Ali Esfandiari; Cena Aram; Alia Saberi (BMC Infectious Diseases)
Abstract Introduction Vaccination is considered as one of the most promising strategies to overcome the COVID-19 pandemic. However, it could be associated with rare but serious complications. In the present study, we aimed to review the clinical course and etiology of post COVID-19 vaccination meningitis. Methods After a systematic search in PubMed, Scopus, and Web of Sciences online databases as well as Google Scholar, documents were screened and qualified. Then data extraction was performed and the most frequent underlying agent of meningitis was found based on the reported cases. Results Overall, 35 cases of post COVID-19 vaccination meningitis from 33 articles were included in the review. Among them, 12 cases had proven viral diagnosis and 23 of them were reported to be vaccine-induced. The most frequent viral pathogen among the cases was VZV. The most prevalent symptom was headache, and the most common time of appearance symptoms was one week after vaccination. Conclusion Overall, our study suggested meningitis as a critical but not devastating complication of COVID-19 vaccination. Almost all patients responded well to common agents used to manage viral or vaccine-induced meningitis. It is recommended to monitor patients with a history of chickenpox after COVID-19 vaccination regarding the development of meningitis.